Studi Komparasi Beberapa Pengendali untuk Pengontrolan Lampu Lalu Lintas Dua Persimpangan Berdekatan - Muhammad Yudha Permana; Muhammad Rizal Taufik; Fuzi Fauzia Ahmad; Muhammad Fahmi Ibrahim (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
The purpose of this research is to design a traffic light system that has an effective timing of the color change of lights, design a system that can regulate traffic lights using a Counter system, adaptive fix timer, semi-intelligent controller, and Vehicle Actuated Controller to calculate vehicle density on a lane in two intersections that are close together so that there is no buildup of vehicles on the lane, and compare all the systems made so that it can be known which system is superior. Counter system, Adaptive Fix Timer, Semi Intellegent Controller, and Vehicle Actuated Controller are PLC (Programmable Logic Controller) instructions that are made using the Cx - programmer application to control the traffic lights on the two crossing simulators that are connected serially with the Atmega2560 microcontroller. contained in the hardware interface. Each system has advantages over other systems under certain conditions, each system has a different average waiting time - a counter system of 8.04164, an Adaptive Fix Timer system 10.82615, a Semi Intellegent Controller system 9.99704, and a Vehicle Actuated system Controller 11.34686. The design of the two crossing simulators was made using the LabVIEW application which was controlled using a PLC and the comparison of each system was successfully carried out